Impact of the âCreche com Sabor e SaÃºdeâ (C2S) project on the food provided by Portuguese daycare centers - Olívia Pita; Beatriz Teixeira; Lúcia Nova; Beatriz Cidade Coelho; Inês Dias; Mariana Conceição; Liliana Ferreira; Ana Jorge; Maria do Céu Monteiro; Maria Cristina Teixeira Santos; Sara Rodrigues; Ada Rocha; et al. (Portuguese Journal of Pediatrics, 2025)
Introduction and Objectives: To assess the impact of implementing a community intervention project on the food offered at lunch in Portuguese daycare centers. Methods: A study was conducted in a nonprobabilistic, convenience sample of 18 Portuguese daycare centers that welcome children from six to 36 months old. The characterization of the institutions was developed using a self-administered online questionnaire. To evaluate the menu, a qualitative analysis tool was created. After an initial assessment of 12 weeks of menus in each institution, the intervention lasted for nine months. This entailed the preparation of individualized technical reports and the close monitoring of the daycare centers. A further application of the menu analysis tool was subsequently conducted for the final 12 weeks of the project. The impact of the intervention was estimated by the difference between the results obtained before and after the intervention. Results: Following the intervention, there was an improvement in the description of meal components and the overall quality of the menus, which was improved by 16%. Throughout the study, the number of facilities with a lunch menu for the six to eight months age group increased from 13 to 16, while the number of times cooked fruit was offered decreased by a median of 100% in the institutions. In the nine to 11 months age group, there was a median of 100% of institutions beginning to offer only one type of pureed fruit. In the 12 to 36 months age group, the number of times that oily fish was offered, as well as vegetables, in addition to the carbohydrate source increased in a median of 8.3% of the institutions. Discussion: Despite the simplicity and duration of this intervention, there was an improvement with compliance with recommendations, including a decrease in the number of times cooked fruit was offered in the six to eight months age group and an increase in the number of times oily fish was offered in the 12 to 36 months age group.